PENGARUH KESELARASAN GAYA HIDUP DAN NILAI BIAYA YANG DIRASAKAN TERHADAP LOYALITAS MEREK YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PENGGUNA MEREK WARDAH KOSMETIK DI KOTA BANDA ACEH - intan juwita alam; Abdul Rahman Lubis (Departemen Manajemen, 2023)
This study aims to measure the effect of Lifestyle Congruence and Perceived Value of Cost on Brand Loyalty mediated by Customer Satisfaction on Wardah Cosmetics consumers in Banda Aceh. The sample used in this study were Wardah Cosmetics consumers, totaling 200 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used is purposive sampling. Structural Equation Modeling (SEM) is used as an analytical method to determine the effect between the variables involved. Based on the results of SEM analysis identified that Lifestyle Congruence has a positive effect on Brand Loyalty, Perceived Value of Cost has a positive effect on Brand Loyalty, Lifestyle Congruence has a positive effect on Perceived Value, Perceived Value of Cost has a positive effect on Customer Satisfaction, Customer Satisfaction fully mediates the influence of Lifestyle Congruence on Brand Loyalty, and Customer Satisfaction fully mediate the influence of the Perceived Value of Cost on Brand Loyalty.